Trends and Themes in Halal Industry Research: A Scientometric Study Based on Scopus Publications - Judijanto, Loso; Ru'yat, Ru'yat (West Science Islamic Studies, 2025)
This study examines global trends, topic development, and collaborative networks in halal sector research through a scientometric analysis of Scopus publications from 2000 to 2025. The analysis, utilizing VOSviewer and Biblioshiny for data visualization, reveals four predominant research clusters: halal food, halal tourism, supply chain management, and sustainability. The findings indicate a transition from conventional issues of religious adherence and certification to modern topics including digital innovation, ethical consumption, and sustainable business practices. Malaysia and Indonesia are the primary suppliers, bolstered by robust institutional networks involving Universiti Teknologi MARA, International Islamic University Malaysia, and Universitas Gadjah Mada. Notwithstanding increasing regional collaboration, global participation is predominantly concentrated in Southeast Asia, with minimal involvement from Western and African institutions. This study enhances theoretical development by delineating the intellectual framework of halal research and provides practical implications for policymakers and industry stakeholders aiming to amalgamate halal principles with sustainability, governance, and technological progress.